2018
DOI: 10.3390/ijms19071871
|View full text |Cite
|
Sign up to set email alerts
|

Using microRNA Networks to Understand Cancer

Abstract: Human cancers are characterized by deregulated expression of multiple microRNAs (miRNAs), involved in essential pathways that confer the malignant cells their tumorigenic potential. Each miRNA can regulate hundreds of messenger RNAs (mRNAs), while various miRNAs can control the same mRNA. Additionally, many miRNAs regulate and are regulated by other species of non-coding RNAs, such as circular RNAs (circRNAs) and long non-coding RNAs (lncRNAs). For this reason, it is extremely difficult to predict, study, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 88 publications
1
66
0
Order By: Relevance
“…9 It is well documented that miRNAs are aberrantly expressed and participate in the pathogenesis of various human disorders, including cancer. [10][11][12] The dysregulation of miRNAs has been detected in nearly all human cancer types, and may play either tumor-suppressive or oncogenic roles, which mainly depend on the characteristics of their target genes. [13][14][15] Many miRNAs have previously been reported to be downregulated or upregulated in PDAC, and their deregulation is involved in the control of cancerrelated biological behaviors, including cell proliferation, cell cycle distribution, apoptosis, metastasis, and resistance to radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…9 It is well documented that miRNAs are aberrantly expressed and participate in the pathogenesis of various human disorders, including cancer. [10][11][12] The dysregulation of miRNAs has been detected in nearly all human cancer types, and may play either tumor-suppressive or oncogenic roles, which mainly depend on the characteristics of their target genes. [13][14][15] Many miRNAs have previously been reported to be downregulated or upregulated in PDAC, and their deregulation is involved in the control of cancerrelated biological behaviors, including cell proliferation, cell cycle distribution, apoptosis, metastasis, and resistance to radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs negatively modulate gene expression through direct binding to the 3-untranslated regions (3'-UTRs) of target genes, thus leading to translational inhibition and/or mRNA degradation (9). miRNAs not only serve crucial roles in regulating various fundamental cellular processes but are also closely associated with tumorigenesis and tumor development (10,11). Previous studies have reported that miRNAs are aberrantly expressed in almost all types of human cancer, including PTC (12), colorectal cancer (13), lung cancer (14), glioblastoma (15) MicroRNA-766 inhibits papillary thyroid cancer progression by directly targeting insulin receptor substrate 2 and regulating the PI3K/Akt pathway and bladder cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al (31) demonstrated that Sulfatase 2 (SuLF2) could enhance cell proliferation, invasion, mobility and adhesion, and suppress apoptosis of BCa cells, which suggests that SuLF2 may be a therapeutic target for BCa treatment. Over the past decades, a number of studies have reported important roles of miRNAs in numerous types of human cancer (32)(33)(34). In addition, miRNAs have been described as functional molecules during the progression of various types of malignancy, including BCa (35).…”
Section: Discussionmentioning
confidence: 99%